DEVELOPMENT OF CRITICAL THINKING AND PROBLEM SOLVING SKILLS IN PRIMARY STUDENTS - Abdulborieva Mehruza Anvarovna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article is aimed at developing critical thinking and problem solving skills in primary school students. The article considers the importance of critical thinking, its role in primary education, as well as methods that promote its development. To develop critical thinking, teachers are recommended to organize activities based on modern pedagogical methods, group work, discussions, interactive technologies and problem situations. The article emphasizes that the development of critical thinking helps students not only in mastering knowledge, but also in making the right decisions in various life situations.